Synthesis, structure and hydrogen sorption properties of a pyrazine-bridged copper(I) nitrate metal-organic framework - Nfor, Emmanuel Ngwang; Burrows, Andrew David; Ndosiri, Bridget Ndoye; Keenan, Luke Lawrence; Offiong, Offiong Efanga (European Journal of Chemistry, 2019)
A new copper(I) pyrazine-bridged coordination polymer [Cu2(pyz)3(NO3)2]·2DMF] (pyz = pyrazine) (1) has been synthesized and characterized by FT-IR, TG/DTG, DSC and single crystal X-ray diffraction techniques. The X-ray crystallographic result reveals a two-dimensional network structure containing hexagonal pores. Thermal analysis of compound 1 reveals it is stable to 380 °C, and gas sorption studies showed that it adsorbs 1.04 wt% hydrogen at 1 atm and 77 K. Compound 1 crystallizes in a triclinic system, space group P-1 (no. 2), a = 7.9550(2) Å, b = 7.9810(2) Å, c = 11.0660(3) Å, α = 76.328(1)°, β = 71.115(1)°, γ = 84.577(1)°, V = 645.79(3) Å3, Z = 2, T = 150(2) K, μ(MoKα) = 1.709 mm-1, Dcalc = 1.639 g/cm3, 11111 reflections measured (7° ≤ 2Θ ≤ 54.96°), 2951 unique (Rint = 0.0539) which were used in all calculations. The final R1 was 0.0346 (>2σ(I)) and wR2 was 0.0727 (all data).